Seen but not heard: a systematic review of the place of the child in 21st-century dental research - ZOE MARSHMAN, BARRY J. GIBSON, JANINE OWENS, HELEN D. RODD, HUW MAZEY, SARAH R. BAKER, PHILIP E. BEN (IAPD and Blackwell, 2007)
‘Children seen, but not heard’ is a saying that originated from early Victorian times. During such times, children did not have a childhood as we know it today; they were seen as ‘imperfect’ adults, wearing smaller versions of adult’s clothes and went to work rather than school.